2020
DOI: 10.1007/s11469-020-00339-4
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Feeling Valued Versus Expendable During the COVID-19 Pandemic and Beyond: a Review and Commentary of Why Mattering Is Fundamental to the Health and Well-Being of Older Adults

Abstract: The current commentary and review examines the potentially protective role of feelings of mattering among elderly people during typical times and the current atypical times associated with the COVID-19 global pandemic. Mattering is the feeling of being important to others in ways that give people the sense that they are valued and other people care about them. We contrast this feeling with messages of not mattering and being expendable and disposable due to ageism, gaps in the provision of care, and apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 83 publications
6
96
1
5
Order By: Relevance
“…This expectation was supported because students in this study reported less loneliness and fewer loneliness-related thoughts if they had higher levels of mattering and without the feeling and fear of not mattering to others. These results are in keeping with broad calls to promote feelings of mattering to help people cope with the isolation and other stressors and strains associated with living through the current global health crisis (see Flett and Heisel 2020;Flett and Zangeneh 2020).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This expectation was supported because students in this study reported less loneliness and fewer loneliness-related thoughts if they had higher levels of mattering and without the feeling and fear of not mattering to others. These results are in keeping with broad calls to promote feelings of mattering to help people cope with the isolation and other stressors and strains associated with living through the current global health crisis (see Flett and Heisel 2020;Flett and Zangeneh 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Self-esteem and mattering were included as another main focus given general evidence of the benefits of self-esteem and mattering in adapting to life challenges (see Flett 2018). A series of analyses have underscored a sense of mattering to others as being vital in helping people adjust to the stress and psychosocial challenges arising out of being physically isolated and feeling socially isolated (see Casale and Flett 2020;Flett and Heisel 2020;Flett and Zangeneh 2020). These analyses-as well as work with the Anti-Mattering Scale (see Flett 2018)-further highlight that just as mattering is protective as a key element of self-worth experiences, marginalization experiences and feelings of not mattering contribute to feelings of stress and distress.…”
mentioning
confidence: 99%
“…Media coverage plays an important and direct role in shaping official responses to unfolding crisis situations and often operates to promote greater social control of already structurally disadvantaged groups (Tierney et al 2006). It also helps to convey who matters during crises and who are thus legitimate recipients of community and government support (Flett 2020).…”
Section: Introductionmentioning
confidence: 99%
“…B. auch in Form der emotionalen Unterstützung anderer) und die Wichtigkeit des eigenen Lebens für andere wurden von der Zielgruppe nur wenig reflektiert. Ein aktuelles Review zum Konzept der Wichtigkeit beschreibt das Erleben einer Person, für jemand anderen von Bedeutung zu sein, als einen wichtigen protektiven Faktor und als wesentlich für funktionales Coping und Resilienz im Zusammenhang mit der COVID-19-Pandemie [ 21 ].…”
Section: Diskussionunclassified